2020
DOI: 10.1002/jcp.30073
|View full text |Cite
|
Sign up to set email alerts
|

Deficient muscle regeneration potential in sarcopenic COPD patients: Role of satellite cells

Abstract: Sarcopenia is a major comorbidity in chronic obstructive pulmonary (COPD). Whether deficient muscle repair mechanisms and regeneration exist in the vastus lateralis (VL) of sarcopenic COPD remains debatable. In the VL of control subjects and severe COPD patients with/without sarcopenia, satellite cells (SCs) were identified (immunofluorescence, specific antibodies, anti‐Pax‐7, and anti‐Myf‐5): activated (Pax‐7+/Myf‐5+), quiescent/regenerative potential (Pax‐7+/Myf‐5‐), and total SCs, nuclear activation (termin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
31
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 65 publications
(148 reference statements)
1
31
0
1
Order By: Relevance
“…All studies demonstrated that repetitive bouts of exercise over time (training) promotes changes in muscle architecture, capillarisation and myogenesis in younger and older participants, consistent with other studies [ 4 , 13 , 17 , 54 , 58 ]. Despite the variability regarding participant sex, age and exercise type/duration, muscle remodelling was accompanied by ECM adaptation.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…All studies demonstrated that repetitive bouts of exercise over time (training) promotes changes in muscle architecture, capillarisation and myogenesis in younger and older participants, consistent with other studies [ 4 , 13 , 17 , 54 , 58 ]. Despite the variability regarding participant sex, age and exercise type/duration, muscle remodelling was accompanied by ECM adaptation.…”
Section: Discussionsupporting
confidence: 89%
“…Myostatin regulates myogenesis and inhibits muscle mass by maintaining satellite cell quiescence. Recently, the group of Barreiro demonstrated that sarcopenic muscle from COPD patients is characterised by increased levels of myostatin compared to non-sarcopenic controls [ 58 ]. However, the levels of decorin and fibronectin in sarcopenic muscle after exercise training is not known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nutritional evaluation included the assessment of body mass index (BMI) and determination of fat-free mass index (FFMI) using bioelectrical impedance [ 13 , 17 , 28 , 29 , 30 ]. Blood analytical parameters (systemic inflammatory cells and markers) were also obtained in all participants.…”
Section: Methodsmentioning
confidence: 99%
“…Blood analytical parameters (systemic inflammatory cells and markers) were also obtained in all participants. Lung function parameters were determined in all study subjects following standard procedures [ 13 , 17 , 28 , 29 , 30 ]. Exercise capacity was assessed through the 6-min walking distance following previous methodologies [ 31 ].…”
Section: Methodsmentioning
confidence: 99%